Percutaneous Closure of a Prosthetic Pulmonary Paravalvular Leak. (22nd April 2013) - Seery, Thomas J.; Slack, Michael C.
Abstract Paravalvular leak following prosthetic valve surgery has the potential to cause serious complications such as hemolysis and congestive heart failure. Successful percutaneous closures of prosthetic mitral and aortic paravalvular leaks have been performed as an alternative to reoperation. This case represents the first known report of successful percutaneous closure of a prosthetic pulmonary paravalvular leak in an adult patient with a history of congenital heart disease using two muscular ventricular septal defect occluder devices.